RADICAL REACTIONS IN SYNTHESIS - INTRAMOLECULAR SH2' MACROCYCLISATIONS - Baldwin, J; Adlington, R; Mitchell, M; Robertson, J (1990)
The synthesis of 10-15 membered α-methylene lactones 1 from the functionalised allyl stannanes 2 occurs cleanly in moderate to high yield under free radical conditions via an intramolecular SH2′ reaction.